The Effectiveness of Silicon Wound Dressing for the Healing Process of Contaminated Abrasions - Limpat Wihastyoko, Herman Yosef; Siswoyo, Devira; Arviansyah, Arviansyah; Siswanto, Yudi; Agustina, Wilma; Sintaningrum, Elisabeth Prajanti (Fakultas Kedokteran Universitas Brawijaya, 2024)
Wounds are skin disorders caused by pathological processes. Abrasion wounds are a type of acute injury. One of the contributing factors is traffic accidents. More than 1.2 million people died as a result of traffic accidents, while 20-50 million others suffered injuries. Choosing the proper dressing can determine wound healing. This case study aims to determine the effectiveness of silicone wound dressing in the healing process of contaminated abrasion wounds. Contaminated abrasion wounds are contaminated by dirty materials, which potentially cause infection. This case report describes four patients, Mrs. W, Mrs. K, Mr. Y, and Mr. M., who suffered abrasions on the face. Their wounds were cleaned in the operating room under general anesthesia. A silicone wound dressing is applied as the primary dressing. The secondary dressing depends on the amount of the exudate. On the 3rd day after the surgery, the wounds looked dry, so they were cleaned and reapplied with the silicone dressing. On the 7th day, after applying silicone wound dressing, the wound had epithelialized. Silicone wound dressing is a modern type of dressing that is effective for acute wounds as it provides a barrier against external contamination. Our sample shows that wound are abrasion contaminated. The result of silicone wound dressings applied was shown accelerate the wound healing process. Modern dressings accelerate wound healing 20% to 40% faster than conventional dressings, such as gauze, tulle, or gauze.